2001
DOI: 10.1097/00129492-200107000-00011
|View full text |Cite
|
Sign up to set email alerts
|

Targeted Topical Steroid Therapy in Sudden Sensorineural Hearing Loss

Abstract: Targeted topical steroid administration avoids the significant systemic side effects of oral steroids and may offer more effective dosing than simple transtympanic injection of medicine. Although these findings are preliminary, it is possible that after further study, targeted drug delivery may be a useful technique to consider in patients with severe to profound hearing loss that have failed all other management options.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
166
1
5

Year Published

2005
2005
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 159 publications
(182 citation statements)
references
References 15 publications
10
166
1
5
Order By: Relevance
“…In humans, although a variety of experimental catheter systems have been employed, the round window microcatheter from DURECT (RWμCath ™ , DURECT ™ , Co., Cupertino, USA) represents the best characterised system to date (10,13,27,48). In a recent nonconcurrent cohort study it was found that local continuous glucocorticoid delivery via the μCath in patients with acute severe or profound hearing loss and failure of standard systemic therapy showed a significant improvement in hearing compared to a historical control group without local treatment (16).…”
Section: Ii) Continuous or Discontinuous Drug Application Via Partly mentioning
confidence: 99%
See 1 more Smart Citation
“…In humans, although a variety of experimental catheter systems have been employed, the round window microcatheter from DURECT (RWμCath ™ , DURECT ™ , Co., Cupertino, USA) represents the best characterised system to date (10,13,27,48). In a recent nonconcurrent cohort study it was found that local continuous glucocorticoid delivery via the μCath in patients with acute severe or profound hearing loss and failure of standard systemic therapy showed a significant improvement in hearing compared to a historical control group without local treatment (16).…”
Section: Ii) Continuous or Discontinuous Drug Application Via Partly mentioning
confidence: 99%
“…Gentamicin is toxic to the sensory cells of the balance system and thereby suppresses the vertigo in these patients by partially ablating their vestibular system. There are also an increasing number of clinical reports related to the local application of glucocorticoids for acute hearing loss (9,10,11,12,13,14,15,16), glucocorticoids for Menière's disease (17,18,19,20) or for tinnitus (21,22,23,24,25). Other substances that have been tested in humans include local anaesthetics, neurotransmitters and neurotransmitter antagonists (26,27).…”
Section: Introductionmentioning
confidence: 99%
“…Despite the practicality in treating patients with a single intratympanic injection of steroids, Fig. 1 Comparison of pretreatment and posttreatment DPOAE amplitudes of group two animals (Mean ± SD 24 ± 4.6) this protocol may not be as optimal as a continuous infusion or multiple injections [22,23].…”
Section: Discussionmentioning
confidence: 99%
“…Sockalingam et al reported that the recording of DPOAE is a sensitive method for the evaluation of the functional state of OHCs and albino guinea pigs are the most sensitive animals in term of cisplatin ototoxicity, with alteration in DPOAE and damage to OHCs [23,24]. Evoked OAE, especially DPOAEs due to frequency specificity, were shown to be more sensitive for evaluating OHCs than were conventional audiometry, ultra high frequency audiometry, and auditory brainstem response [25].…”
Section: Discussionmentioning
confidence: 99%
“…Other authors have also described the use of intratympanic corticosteroids for the treatment of SHL. 9,[12][13][14][15][16][17][18][19][20][21][23][24][25][26][27] Although its efficacy alone has not been proved definitively, intratympanic corticosteroid therapy for SHL is becoming more widely used. The variability among treatment protocols for SHL also applies to intratympanic corticosteroid therapy.…”
Section: Intratympanic Therapymentioning
confidence: 99%